Customers’ Accounts Receivable Late Submission to Curator of Insurance Companies Facing Banckruptcy (Bumi Asih Jaya Insurance Bankruptcy Case) - Anisa Retno Kusumadewi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2019)
This is a normative juridical legal research, i.e a research that examines applicable laws and regulations. Decision of the Supreme Court Number 408 K/Pdt.Sus-Pailit/2015 granted a request for bankruptcy by the Financial Services Authority (OJK) because the application fulfilled the bankruptcy requirements as Article 2 paragraph (1) of the Bankruptcy Law which states that the Debtor has two or more Creditors and does not pay at least one debt that has matured and can be billed, is declared bankrupt with a court decision, both on its own request and on the request of one or more creditors. In 2016, Curator also invited creditors and policy holders of PT Asuransi Jiwa Bumi Asih Jaya to attend the first creditor meeting. Policyholders submitted bills to the curator with the deadline for submitting bills on August 30, 2016. Until today, not all of the policyholders of PT Asuransi Bumi Asih Jaya have been paid by the policy and most of them have not received information about bankruptcy assets carried out by the curator. The author examines two points, first the customer position as the insurance policy holder if the insurance company is bankrupt and their legal ffforts as the holders the policy if the insurance company is bankrupt and are late in registering the receivables to the Curator. The customers’ position is viewed from the perspective of Civil Law and Insurance rules, through the principle of lex specialis derograt legi generali, its position as policyholder is included in the preferred creditor. Legal remedies can be taken by the insurance policy holder to the curator because after a company is bankrupt, the bankruptcy is the responsibility of the curator.